SISTEM PENDIDIKAN SURAU : KARAKTERISTIK, ISI DAN LITERATUR KEAGAMAAN - Maimunah Manaf (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2012)
Education is something that is needed in everyday life. in management education is necessary to everyone, departure from the elaboration above, it is understood that the first mosque was a Minangkabau traditional institution that has two functions, namely education and social issues. In the next stage of development, Muslims make surau as an Islamic educational institutions which have the characteristics, content and religious literature which are very urgent. Thus, the effort to realize the desire to return to the surau that continues to reverberate recently, can not rule out the characteristics, content and literature. Therefore, the last education has not been spreaded to other parts of Minangkabau area. Because there are many differences of opinion of some scholars in the vicinity. With the assurance of the strength and presence in the communities in Minangkabau and the scholars who come there so education in minangkabau now is becoming a center of science, among others: the science of jurisprudence, tasauf, shorop and Nahwu. In the first surau education that is given by Sheikh Burhanuddin which serves as the first Islamic educational institution providing Islamic education in a more orderly system (ie in accordance with the system of Sheikh Abdur Rauf, his teacher in Aceh. Nevertheless, in the historical record there is no information about What Al kitab firstly taught and connected to the graduation level. At the beginning, teaching and learning of Islam has held Islamic studies thoroughly and deeply. At the top level of the teaching of Al Kitab, mostly with halaqah system at that time was divided into two parts, namely teaching upper level and lower level, to lower levels such as Alif ba 'ta' sa 'and juz amma, while for upper level science tasauf lectures and Al Qur'an.